Pengaruh Job Satisfaction dan Organizational Commitment terhadap Kinerja Kerja Mahasiswa yang Bekerja Part-Time di Universitas Muhammadiyah Bandung - Asep Rizal Maulana; Panji Setia Meijaya; Sofa Parihah Nuraisha (Indo Publishing, 2026)
This study aims to analyze the effect of Job Satisfaction and Organizational Commitment on the Work Performance of university students who work part-time at Universitas Muhammadiyah Bandung, both partially and simultaneously. The research is motivated by the growing phenomenon of students juggling dual roles as part-time workers and full-time students, along with a research gap in the literature, as most prior studies focus on permanent employees while research on part-time student workers remains limited. This study employs a quantitative approach with an associative-causal research design. Data were collected through questionnaires distributed to 84 active university students who were currently or had previously worked part-time, using a purposive sampling technique, and analyzed using multiple linear regression via SPSS. The results show that Job Satisfaction has a positive and significant effect on Work Performance (t = 3.487; Sig. < 0.001), Organizational Commitment has a positive and significant effect on Work Performance (t = 3.644; Sig. < 0.001), and both variables simultaneously have a positive and significant effect on Work Performance (F = 23.132; Sig. < 0.001), contributing 36.4% (R² = 0.364) to the variance in Work Performance. These findings indicate that although secondary in nature, job satisfaction and organizational commitment remain important drivers of performance among part-time student workers. This study contributes theoretically to the development of organizational behavior research in part-time work contexts, and practically by informing employers on how to foster working conditions that support satisfaction, commitment, and performance.